Primeiros registros de estruturas reprodutivas vegetais e sementes da formação serra do tucano (cretáceo inferior), bacia do tacutu, roraima - Trajano, Adriana de Souza (2022)
The Tacutu Basin is located in a border region between Brazil (northeast of the state of Roraima) and Guyana. Its origin is related to the Central Atlantic opening and presents in its composition Mesocenozoic sediments. The plant macrofossils (seeds and reproductive structures) are compressions/impressions, preserved in sandstones with parallel plane lamination from the Murici II outcrop, belonging to the Serra do Tucano Formation (Barremian-Aptian). The research aimed to: (i) describe seeds and reproductive structures comparing them with species already described in the literature, (ii) carry out studies on diaspore size and dispersal strategies, (iii) make paleoecological inferences from the records studied. Initially, the screening of plant macrofossils was carried out, later the selected specimens were analyzed and photographed. The analyzes and interpretations of the samples resulted in the focus of the morphological features of the reproductive structures (n=5), for taxonomic study purposes and seed size analyzes (n=48), for paleoecological inferences. The results obtained here suggest that the reproductive structures belong to the Ephedraceae group and comprise a vegetation of xerophytic plants typical of the dry and hot climate of the Barremian-Aptian interval. While the analysis of the average size of the seeds showed a predominance of sizes less than or equal to 10mm³, which corroborates data already reported for the Early Cretaceous, where the seeds were small and indicative of more open vegetation and dry climatic conditions.